Proton-detected solid-state NMR of the cell-free synthesized α-helical transmembrane protein NS4B from hepatitis c virus - Jirasko, Vlastimil; Lakomek, Nils-Alexander; Smith-Penzel, Susanne; Fogeron, Marie-Laure; Bartenschlager, Ralf; Meier, Beat H.; Böckmann, Anja (ChemBioChem, 2020)
Abstract Proton-detected 100?kHz magic-angle-spinning (MAS) solid-state NMR is an emerging analysis method for proteins with only hundreds of microgram quantities, and thus allows structural investigation of eukaryotic membrane proteins. This is the case for the cell-free synthesized hepatitis?C virus (HCV) nonstructural membrane protein 4B (NS4B). We demonstrate NS4B sample optimization using fast reconstitution schemes that enable lipid-environment screening directly by NMR. 2D spectra and relaxation properties guide the choice of the best sample preparation to record 2D 1H-detected 1H,15N and 3D 1H,13C,15N correlation experiments with linewidths and sensitivity suitable to initiate sequential assignments. Amino-acid-selectively labeled NS4B can be readily obtained using cell-free synthesis, opening the door to combinatorial labeling approaches which should enable structural studies.
First published: 18 December 2019
Gesehen am 03.07.2020